Recurrent prosthetic valve dysfunction in a patient with idiopathic hypereosinophilic syndrome: A case report and literature review. Issue 11 (21st August 2021) - Wei, Zhipeng; Guo, Hongchang; Li, Jinhua; Lai, Yongqiang
Abstract: Idiopathic hypereosinophilic syndrome with cardiac involvement is characterized by endocardial fibrosis and thrombosis. Here, we report a case of mitral valve prosthetic dysfunction in a patient with idiopathic hypereosinophilic syndrome and review related cases in the literature. Valve replacement with a 27‐mm St. Jude bioprosthetic mitral valve improved his symptoms and hypereosinophilia. A 4‐year follow‐up revealed that the prosthetic valve was intact without thrombosis. Because mechanical prosthesis implantation yields poor surgical outcomes, bioprosthesis is the preferred choice for patients with idiopathic hypereosinophilic syndrome. Medications for controlling eosinophilia may improve the long‐term outcomes of valve replacement surgeries.